(untitled) (Revista educación, investigación, innovación y transferencia, 2022)
This article describes and analyzes a teaching activity put into practice during the last decade in the Bachelor’s in Medicine, the so-called Tutored Works, whose methodology, objectives and results we consider to be of interest to professors and students both in the field of the Health Sciences and of the Humanities and Social Sciences. These works are carried out in small groups within the 1st year course in “Research and New Technologies” and consist of conducting a personal interview with a former student of the Faculty of Medicine and processing the collected data to obtain an oral source useful for future research and to preserve the institution’s historical memory. Among the conclusions obtained we highlight: 1) acquisition of a more complex image of the medical profession; 2) difficulty of fitting an activity of research initiation into an intensive academic calendar; 3) problems in understanding qualitative methodologies in a biomedical context.